Fatty Acid Composition of Lipid Extracts of a Thermophilic Bacillus Species - Daron, Harlow H. (1970)
Fatty acids having 16 or 17 carbon atoms accounted for over 80% of the fatty acids produced by a thermophilic Bacillus species. Under most conditions, branched-chain fatty acids were more abundant than normal fatty acids. The proportion of unsaturated fatty acids varied inversely with the growth temperature and was never greater than 14%. When acetate was used as a carbon source, the percentage of fatty acids having 15 or 17 carbon atoms was about twice that found when glucose was used as a carbon source. Increasing the growth temperature from 40 to 60 C resulted in a three-to fourfold increase in the ratio of the normal to branched-chain hexadecanoic acids. Two normal hexadecenoic acids were found and their relative abundance was influenced by the growth temperature.